Geographic Information System for Mapping Tourism and Small Micro Enterprises Medium in Sorong City, Southwest Papua Web-Based - Rajagukguk, Iriene Surya (JURNAL PETISI (Pendidikan Teknologi Informasi), 2024)
Geographic Information System (GIS) is one of the solutions to get information about the location of tourist sites in the city of Sorong. Tourism in Sorong City is an object that is used as material for this research, because Sorong City has great potential in the field of tourism that presents tourist attractions for local and international tourists. Tourist attractions in Sorong City include Marina Tourism, Tirta Tourism, Historical Tourism, and Nature Reserve Tourism.